2021
DOI: 10.1021/acsapm.1c00997
|View full text |Cite
|
Sign up to set email alerts
|

Photocurable Three-Dimensional Printing Resin to Enable Laser-Assisted Selective Electroless Metallization for Customized Electronics

Abstract: Integrating conductive metal patterns directly on three-dimensional (3D) printed polymers is crucial for realizing diverse 3D printing applications. In this study, we developed photocurable 3D printing resins incorporating ZnO nanoparticles (3DP-ZnO) for 3D printed structures, which enabled subsequent copper (Cu) electroless plating (ELP). ZnO nanoparticles (NPs) were incorporated in the resin as catalytic seeds for ELP, and Cu patterns were precisely fabricated on 3DP-ZnO after 355 nm UV laser activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Photocuring behavior of the 3D printing resin also plays a vital role in achieving accuracy and fast printability in 3D DLP printing technology. To quantitatively analyze the photocuring behavior of SH6(100), we performed a photocured depth study as described in our previous studies. , The penetration depth ( D p ) and critical energy ( E c ) values of SH6(100) were calculated from the working curves, which were obtained in accordance with Jacob’s equation. , As shown in Figure S2, D p and E c of SH6(100) were estimated to be 565.5 μm and 2.472 mJ/cm 2 , respectively. Taking advantage of the rapid photocuring kinetics of thiol-ene-acrylate polymerizations, our resin system exhibited higher values of D p and lower E c compared to previous systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Photocuring behavior of the 3D printing resin also plays a vital role in achieving accuracy and fast printability in 3D DLP printing technology. To quantitatively analyze the photocuring behavior of SH6(100), we performed a photocured depth study as described in our previous studies. , The penetration depth ( D p ) and critical energy ( E c ) values of SH6(100) were calculated from the working curves, which were obtained in accordance with Jacob’s equation. , As shown in Figure S2, D p and E c of SH6(100) were estimated to be 565.5 μm and 2.472 mJ/cm 2 , respectively. Taking advantage of the rapid photocuring kinetics of thiol-ene-acrylate polymerizations, our resin system exhibited higher values of D p and lower E c compared to previous systems.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier-transform infrared spectroscopy (FT-IR) spectra were analyzed using a Nicolet 6700 spectrometer (Thermo Fisher Scientific) to confirm the surface chemical properties of a printed object. The photocuring depth study was conducted using previously reported procedures. , The thickness of the photocured sample was measured using a Digimicro MS-4G instrument (Nikon). The density of the photocured SH6(100) object was gauged using a ML204 instrument (Mettler Toledo) through Archimedes’ principle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, other approaches such as using polypropylene (PP) doped with multi‐walled carbon nanotubes [ 20 ] or PdCl 2 ‐loaded polyvinylpyrrolidone coatings [ 21 ] as precursors for laser‐induced selective metallization were also reported. In addition, organometallic complexes based on palladium (Pd 2+ ), copper (Cu 2+ ), [ 22 ] as well as metal oxides (ZnO) [ 23 ] and composites of copper–chromium oxide (CuO·Cr 2 O 3 ) or antimony‐doped tin oxide (ATO) [ 24,25 ] have been used as catalyst sources. The active material is finely dispersed in the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%